Effects of long-term diet exposure on decision making in rats - Steele, Catherine C. (Kansas State University, 2017)
Obesity is associated with impaired decision making across a range of choice behaviors including impulsive choice behavior and incentive value. Given that people make approximately 200 food choices each day (Wansink & Sobal, 2007), it is essential to better understand this relationship between obesity and impaired decision making. As such, the current study sought to understand how long-term exposure to diets high in processed fat and sugar affected impulsive choice behavior, devaluation, and food preferences. The results suggested that diet affects impulsive choice behavior. Rats exposed to diets high in processed fat or sugar were more sensitive to changes in delay, a marker of impulsivity. Results from the bisection task indicated that the diet-induced impulsivity could be a result of poor time discrimination. In addition, there were differences in incentive value. All rats successfully devalued rewards, but the high-fat and high-sugar group showed lower overall levels of responding. Further, diet-induced impulsivity could lead to overconsumption of high-fat and high-sugar foods due to differences in food preference. After 9 months on the diets, rats fed a chow and high-sugar diet displayed a sugar preference, while the rats fed a high-fat diet displayed a fat preference. Together, the results suggest that the alterations in impulsive choice and incentive valuation induced by diet could make individuals vulnerable to overeating, and thus obesity, as well as other disorders that are characterized by impulsive choice and deficits in incentive valuation.
Keywords: Impulsive choice; Devaluation; Preference; Decision making; Diet; Rats